2018
DOI: 10.21873/invivo.11298
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy with Pyoktanin Blue and Diode Laser for Elimination of Enterococcus faecalis

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 25 publications
0
12
0
3
Order By: Relevance
“…Em seguida, como medida para aumentar a eficácia da desinfecção foi empregado o azul de metileno 0,010% (Chimiolux) preenchendo toda a janela óssea e associando ao laser infravermelho de baixa potência, atuando assim como terapia fotodinâmica gerando a liberação de radicais livres que proporcionam efeito bactericida (Souza et al, 2019). A utilização do laser de baixa frequência é segura, de fácil manipulação e aceitação pelo paciente, técnica seletiva além de promover atividade antimicrobiana quando associado a um corante fotossensibilizador, não causa efeitos sistêmicos e não promove resistência bacteriana (Trindade et al, 2017;Souza et al, 2019;Vieira et al, 2018;Masuda et al, 2018). Após análise molecular sobre o efeito antimicrobiano da PDT que quando esta terapia é usada junto às cirurgias endodônticas, o nível de bactérias e estreptococos, presente na cavidade radicular e na superfície de corte, diminuiu significativamente.…”
Section: Discussionunclassified
“…Em seguida, como medida para aumentar a eficácia da desinfecção foi empregado o azul de metileno 0,010% (Chimiolux) preenchendo toda a janela óssea e associando ao laser infravermelho de baixa potência, atuando assim como terapia fotodinâmica gerando a liberação de radicais livres que proporcionam efeito bactericida (Souza et al, 2019). A utilização do laser de baixa frequência é segura, de fácil manipulação e aceitação pelo paciente, técnica seletiva além de promover atividade antimicrobiana quando associado a um corante fotossensibilizador, não causa efeitos sistêmicos e não promove resistência bacteriana (Trindade et al, 2017;Souza et al, 2019;Vieira et al, 2018;Masuda et al, 2018). Após análise molecular sobre o efeito antimicrobiano da PDT que quando esta terapia é usada junto às cirurgias endodônticas, o nível de bactérias e estreptococos, presente na cavidade radicular e na superfície de corte, diminuiu significativamente.…”
Section: Discussionunclassified
“…Estrela, Estrela, Pécora et al (2003) [17], in their study evaluating the needed time for Ca(OH) 2 to eliminate S. aureus, E.faecalis, P. aeruginosa, B. subtilis, C. albicans, concluded that Ca(OH)2 paste was able to eliminate these microorganisms only after 60 days, and the same period for canal infected by a mix of the same microorganisms. The paste of Ca(OH) 2 said to be ineffective as intracanal medication over specific types of microorganisms [6,7], which may necessitate the use of reliable techniques that collaborate in the success of RCT [12].…”
Section: Discussionmentioning
confidence: 99%
“…The aPDT demonstrated antimicrobial effects in various studies using different wavelengths of the low power laser or LEDs, since specific and high absorption by a non-toxic photoactive dye, called a photosensitizer in the presence of oxygen promoting the photochemical reaction and production of reactive oxygen specimens (ROS) like hydroxyl, superoxide anion, Triplet Oxygen and Singlet Oxygen [10], which contributes to microorganisms disinfection. This procedure is a complementary technique beside irrigating solutions or intracanal medications [11,12], as well as being compatible and without thermal side effects over the surrounding tissue [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…During PDT, PS influences the degree of damage. The previous report has shown that diode laser along with Pyoktanin was effective in eradiation of E. faecalis without having any toxicity to human dermal fibroblasts [38].…”
Section: Comparative Studiesmentioning
confidence: 96%